2018
DOI: 10.3389/fpls.2018.00883
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Use Efficiency of Southern South America Proteaceae Species. Are there General Patterns in the Proteaceae Family?

Abstract: Plants from the Proteaceae family can thrive in old, impoverished soil with extremely low phosphorus (P) content, such as those typically found in South Western Australia (SWA) and South Africa. The South Western (SW) Australian Proteaceae species have developed strategies to deal with P scarcity, such as the high capacity to re-mobilize P from senescent to young leaves and the efficient use of P for carbon fixation. In Southern South America, six Proteaceae species grow in younger soils than those of SWA, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
(90 reference statements)
1
14
1
Order By: Relevance
“…Delgado et al [ 30 ] reported that photosynthetic nutrient use efficiency (mainly PNUE and PPUE), is, in general, higher in soil with higher nutrient availability. Our results are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Delgado et al [ 30 ] reported that photosynthetic nutrient use efficiency (mainly PNUE and PPUE), is, in general, higher in soil with higher nutrient availability. Our results are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…At Koywija, the decline in Nothofagus dombeyi -type pollen does not coincide with an increase in Poaceae, but with the appearance and increase in pollen from Lomatia hirsuta . Indeed, Lomatia hirsuta , a low-growing tree, is physiologically adapted to nutrient-poor soils and hydraulic stress (Alberdi, 1995; Delgado et al, 2018) and it has been reported to grow rapidly after fire and grazing or in abandoned farmlands (Donoso and Escobar, 2006; Raffaele and Veblen, 1998). These characteristics make it a potential disturbance indicator; however, the low pollen production requires Lomatia hirsuta to be abundant before the pollen type is registered.…”
Section: Discussionmentioning
confidence: 99%
“…At Koywija, the decline in Nothofagus dombeyi-type pollen does not coincide with an increase in Poaceae, but with the appearance and increase in pollen from Lomatia hirsuta. Indeed, Lomatia hirsuta, a low-growing tree, is physiologically adapted to nutrient-poor soils and hydraulic stress (Alberdi, 1995;Delgado et al, 2018) and it has been reported to grow rapidly after fire and grazing or in abandoned farmlands Pollen percentages in black, ×10 exaggeration light-gray silhouettes. Microscopic charcoal particles expressed as percentage of the terrestrial pollen sum.…”
Section: Changes In Woodland Compositionmentioning
confidence: 99%
“…Mat, Table S2), despite the seeds came from the site with the higher P availability in the soil. Thus, considering the higher or lower capacity of P uptake from the soil and the seed P concentration, these plants can have a further capacity of P translocation to seeds to ensure germination of the next generation (Zúñiga-Feest et al 2015;Delgado et al 2018). More investigations about P use efficiency are necessary to understand this differential performance among populations.…”
Section: N Orchestrate the Cr Formation Induced By P Limitationmentioning
confidence: 99%
“…E. coccineum has a naturally patchy distribution in woodland scrub, typically occurring in gaps, open areas or along roadsides and it is rarely dominant wherever it occurs. (Rodríguez et al 1983;Alberdi and Donoso 2004;Souto et al 2009;Delgado et al 2018).…”
Section: Introductionmentioning
confidence: 99%